PREFIKS DALAM HEADLINE RIAU POS EDISI 10 JUNI SAMPAI 30 JUNI 2016 - Arisandy, Riestha; Faizah, Hasnah; Sinaga, Mangatur (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: This study discusses the form, function and meaning of prefixes in Riau Pos headline edition June 10 to June 30, 2016. This intensive search aims to describe the form, function and meaning of the prefix in headline Riau Pos edition June 10 to June 30, 2016. This research useful practical, theoretical, and educative. This study is a qualitative research and descriptive method. Techniques used in data collection in this study is engineering documentation and technical notes. Data that has been found by reading and then analyzed by several stages of identifying the type, classifying the data, analyze the data and make inferences. Data sourced from the prefix found containing citations identified from a newspaper headline news in Riau Pos is used as a reference in the study. The object of this study is that prefixed words. The results of this study as a contribution for further research about prefixes.Key Words: Prefix, Headline Riau Pos.